2022
DOI: 10.1177/03128962211069615
|View full text |Cite
|
Sign up to set email alerts
|

Does bitcoin liquidity resemble the liquidity of other financial assets?

Abstract: Bitcoin is becoming a popular financial asset and means of transacting. However, little is known about an important aspect of the bitcoin market: its liquidity. We consider whether various dimensions of liquidity evident in other asset classes are present in bitcoin spot and futures liquidity. We find variations in spot liquidity across bitcoin exchanges and a strong commonality in bitcoin spot and futures market liquidity. The pricing of spot and futures bitcoin is relatively inefficient, and liquidity plays … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…Dong et al (2022) found that decreased liquidity led to higher abnormal returns but hindered market efficiency. In their evaluation of the cost of liquidity preference for portfolios combining traditional assets and cryptocurrencies, Moreno et al (2022) demonstrated that considering liquidity made portfolios with the highest expected returns unavailable, which was similarly concluded by Ma et al (2022). Moreover, Wei (2018) discovered that liquidity played a significant role in market efficiency, while Brauneis et al (2022) reported that as liquidity levels increased, the cryptocurrency market became less inefficient.…”
Section: Literature Reviewmentioning
confidence: 94%
See 1 more Smart Citation
“…Dong et al (2022) found that decreased liquidity led to higher abnormal returns but hindered market efficiency. In their evaluation of the cost of liquidity preference for portfolios combining traditional assets and cryptocurrencies, Moreno et al (2022) demonstrated that considering liquidity made portfolios with the highest expected returns unavailable, which was similarly concluded by Ma et al (2022). Moreover, Wei (2018) discovered that liquidity played a significant role in market efficiency, while Brauneis et al (2022) reported that as liquidity levels increased, the cryptocurrency market became less inefficient.…”
Section: Literature Reviewmentioning
confidence: 94%
“…Many studies have explored liquidity and risk management in the cryptocurrency market, employing liquidity measures based on either full orderbook data focusing on BTC (Makarov and Schoar 2019;Brauneis et al , 2022Dyhrberg et al 2018;Marshall et al 2019;Ma et al 2022;Scharnowski 2021) or practical estimators (Manahov 2021;Leirvik 2022;Zhang et al 2020;Al-Yahyaee et al 2020;Wei 2018;Dimpfl 2017;Brauneis et al 2021;Theiri et al 2022;Ghabri et al 2021;Loi 2017;Koenraadt and Leung 2022;Saleemi 2021;Shi 2017;Dong et al 2022;Tang and Wang 2022;Fink and Johann 2014;Moreno et al 2022). However, the dependence structure in cryptocurrency liquidity remains less explored.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These figures correspond to 5% and 12% of the market cap respectfully (CoinGecko). However, research estimates that about 90% of trading volume of Bitcoin is associated with non-economic activity (Makarov and Schoar, 2021 [23]). As for market depth, the estimated free float for Bitcoin (Ether) is 14% (27%) as of January 2022 (based on data from Chainalysis).…”
Section: Economics Of Derivative Holdings Vs Direct Holding Of Cryptomentioning
confidence: 99%
“…Stablecoins are digital assets created, or 'minted', in exchange for fiat currency 23 , and designed to maintain a stable value relative to a national currency or other reference asset (PWG, FDIC and OCC, 2021 [4]). 24 Stablecoins issuance and usage has grown to a multiple of its initial size in a very short time span, reaching nearly USD 120 billion as of 10 February 2022 (see Figure 3.3), although the market for such instruments is highly concentrated in a few issuers (see Figure 3.4).…”
Section: Stablecoins: the Bridge That Links Decentralised To Traditio...mentioning
confidence: 99%